LEVANTAMENTO GEOQUÍMICO ORIENTATIVO PARA FOSFATO NA REGIÃO DE ITATAIA, CEARÁ. - Calado, Bruno; Porto, Claudio; Abram, Maisa (Geochimica Brasiliensis, 2016)
A geochemistry orientation survey was conducted in the vicinity of Itataia uranium-phosphorus deposit in the Ceara state, as part of the Phosphate Project implemented by Geological Survey of Brazil. Data from the geochemical survey in stream sediments from Quixadá sheet, scale 1: 250.000, were processed and interpreted to evaluate in more detail the geochemical response issued by the deposit. Results of the ore, sediment and soil on the scale of detail in the vicinity of the deposit are also reported to study the mobility of metals and their ore-related dispersion. The results for sediment samples of low density analyzed by QQ Plot graphs indicate anomalous points to P and U in the vicinity of the deposit. Geochemical associations showed P associated with the Yb, Th, Lu, Y, Ce, La, Mn e U, well delineated surrounding the deposit. In detail scale, soil samples were analyzed by ICP-MS after multi-acid extraction and tested different size fractions. The transect soil along the slope that hosts the deposit shows a predominantly clastic dispersion up to 850 meters, and highlighted in fractions total and <20 #. The soil on the ore presented be enriched in U, P, Yb, Tb, Lu, La, Ce e Cd compared to soil in regional rocks. The use of paleo-alluvial samples also was tested as sample medium. The paleo-alluvial sediments in the fraction <150 # exhibit high levels of As, Be, Bi, Co, Cr, Cu, Fe, Al, Ga, Li, Ni, Sn, V and Zn, compared to stream sediments. These elements are enriched in ore which reinforces the applicability of paleo-alluvials as sample medium in geochemical exploration.